Dynamics and Dilemmas of Women Leading Women - Bartunek, Jean M.; Walsh, Kate; Lacey, Catherine A. (Organization Science, 2000)
Through examination of transcripts of the first five leadership succession discussions that occurred in a work group designed to empower teachers we explored dynamics and dilemmas associated with women leading a women's group based on feminist principles. We addressed three research questions: How is leadership, as reflected in leadership succession processes, experienced in such a group? What dynamics are associated with leadership succession in this type of group? What are outcomes of the process for members? Results indicated that the experience of leadership shifted considerably during the first six years of the group, with reflective images of leadership moving from the mythical to the pragmatic, from the powerful to the less powerful. Dynamics evolved in ways that were partially consistent and partially inconsistent with organizational life-cycle literature. The group experienced ambivalence and tension surrounding the type of authority given to designated leaders. Members dealt with discomfort by shifting the focus of the group coordinator's attention to external relations and by rotating internal leadership responsibilities. This approach resolved tensions associated with authority and increased members' senses of their own power, even as it decreased the range of initiative-taking that was implicitly allowable within the group. This analysis of leadership succession in a women's group with an empowerment agenda offers a salient case for the study of dilemmas likely to be present in many change efforts. Its results suggest that attempting to resolve contradictions and tensions is less helpful than acknowledging them and working within them.